A proof of concept kilovoltage intensity modulated radiotherapy platform for the treatment of glioblastoma multiforme. (23rd August 2019) - Loughery, Brian; Halford, Robert; Dess, Kathryn; Rakowski, Joseph; Cox, Mary; Koh, Joseph; Mayville, Alan; Riess, Jeffery; Snyder, Michael
Abstract: Purpose : To develop a compact, proof-of-concept kilovoltage intensity modulated radiotherapy platform to deliver contrast-enhanced radiotherapy (CERT). Methods : The proof-of-concept requirements were threefold: (i) develop a compact means to generate a kilovoltage x-ray broadbeam capable of targeting the K-edge of heavy metal contrast, (ii) investigate the potential clinical application of such a beam in silico, and (iii) construct a limited working prototype of the platform to identify weaknesses in the approach. The x-ray broadbeam was created with a standard kilovoltage x-ray tube heavily filtered with 0.156 mm tungsten. Depth dose and treatment characteristics of the beam were investigated using GEANT4 Monte Carlo framework. The working prototype included a miniaturized multi-rod collimator (MRC) constructed with tungsten carbide rods, 3D-printed gear rack, and an in-house GUI/microprocessor assembly. Measurements of simulated treatments were made with EBT3 radiochromic film. Results : Monte Carlo simulations of pseudo-clinical treatments on a homogeneous spherical Lucite phantom produced dose distributions that indicated surface dose was less than target dose. When simulated-bone was added to the calculations, dose-to-bone was found to be the probable limiting factor in clinical treatment. Nevertheless, when iodine contrast enhancement was accounted for, dose was escalated in the tumor compared to standard megavoltage treatments even with dose-to-bone limitations. Experimentally, after commissioning the MRC and calibrating the radiochromic film, surface dose was compared to maximum dose measured on each film. Surface dose measurements were higher than those in a megavoltage beam, but below the skin toxicity threshold. Dose at depth was reasonable despite increased beam attenuation at these energies from photoelectric interactions in bone. IMRT and non-coplanar dose falloffs around the target were steeper than kV 3D conformal dose falloff. Conclusions : The compact kilovoltage treatment platform presented here proved clinically feasible in both simulation and measurement. It is reasonable to pursue this modality further as a potential CERT platform.